Steuerverwaltung in der Ukraine - Petrova, Iryna Pavlivna (Ostinstitut, 2019)
The contribution deals with the historical and organizational aspects of the function of the State Fiscal Service of Ukraine, the existent management levels by the fiscal offices, as well as the structure of the central administrative office, regional offices and tax police. The author places a special emphasis on the competence of agencies SFS offices, tax police and role in the pumping up the state budget, training, retraining and personnel development for fiscal offices and tax police. The strategic axis of the reform of the fiscal offices and improvement of activity by way to European standards are demonstrated.

У науковій статті подаються історичні, правові та організаційні аспекти функціонування Державної фіскальної служби України, існуючі рівні управління у фіскальних органах, а також структура центрального апарату, територіальних органів та податкової міліції. Особливу увагу зосереджено на повноваженнях структурних підрозділів ДФС, підслідності податкової міліції і її ролі в наповненні державного бюджету України, системі підготовки, перепідготовки та підвищення кваліфікації кадрів для фіскальних органів та податкової міліції. Окреслені стратегічні напрямки реформування фіскальних органів та удосконалення діяльності з метою наближення до європейських стандартів.
Keywords: taxation authority; State fiscal service of Ukraine; customs bodies; tax authorities; tax police; reforming; податкове управління; Державна фіскальна служба України; митні органи; податкові органи; податкова міліція; реформування